PDCA METHOD AND CONTRIBUTIONS TO THE DEVELOPMENT OF MICRO AND SMALL BUSINESSES: post-pandemic strategy - Arruda, Marielly Urzêdo; Santos, Micael da Silva; Dutra, Júlio Afonso Alves (Revista Interface Tecnológica, 2022)
This article conceptualizes and presents the execution of the PDCA improvement method, known as the PDCA cycle, a tool that can be used by companies as a continuous improvement strategy. The PDCA is composed of steps, which in its original language means PLAN, DO, CHECK, ACT, which translated into Portuguese is defined as Planejar, Executar, Verificar and Agir. The objective of this study is to demonstrate how the method can contribute to the development of micro and small companies and be considered a post-pandemic strategy, since the pandemic has changed professional relationships and companies have had and are having to adapt to a “new normal". Even with the contributions of the PDCA to companies and the facilities inert to it, there are still some challenges that will be part of the organizational context and that must always be analyzed in order to ensure that the implementation and maintenance of the method occurs effectively and satisfactorily.
Keywords: PDCA; Micro and small companies; Strategy